Solve this equations
![b + c = 0 b + c = 0](https://tex.z-dn.net/?f=b+%2B+c+%3D+0)
![a - 2b - c= 3 a - 2b - c= 3](https://tex.z-dn.net/?f=+a+-+2b+-+c%3D+3)
![- 2b - c = - 1 - 2b - c = - 1](https://tex.z-dn.net/?f=+-+2b+-+c+%3D++-+1)
answerto this equation to be
![(a = \: \: \: 4 )(b = \: \:1 )(c = \: \: - 1 ) (a = \: \: \: 4 )(b = \: \:1 )(c = \: \: - 1 )](https://tex.z-dn.net/?f=%28a+%3D+++%5C%3A++%5C%3A++%5C%3A++4+%29%28b+%3D+%5C%3A++%5C%3A1++%29%28c+%3D++%5C%3A++%5C%3A+-+1+%29)
solve in a detail way please
Answers
Answered by
1
Explanation:
to find :-
b+c =0
a -2b - c=3
-2b-c =-1
given :-
a= 4 , b= 1, c= -1
solutions :-
1 + (-1) =0
1-1= 0
0=0
4-2×1-(-1)= 3
4-2+1=3
5-2=3
3=3
-2×1-(-1)= -1
-2+1 = -1
-1 = -1
Similar questions